Risk Mitigation for Rice Production Through Agricultural Insurance: Farmer’s Perspectives - I Gusti Agung Ayu Ambarawati; I Made Anom Sutrisna Wijaya; I Wayan Budiasa (Jurnal Manajemen & Agribisnis, 2018)
Rice farming is susceptible to failure due to several risks including natural disasters of flood and drought as well as pest and disease attacks. Risk mitigation such as agricultural insurance is required to cope with the risks. This study aims to portray rice production risks to failure and farmer’s perception on the implementation of agricultural insurance in Bali province. Three regencies were selected purposively based on the area insured. A survey was conducted to 180 respondents who paid for the agricultural insurance (AUTP). Data were analyzed using descriptive qualitative analysis and chi-square test. Results of the research show that most rice farming risks to failure in Bali were blast and rat attacks. In terms of agricultural insurance implementation, all farmers accept the program as a mitigation risk to bridge rice farming failure. However, most farmers (85 %) asked for fully support of premium subsidy from the government while the rest agreed to pay for a-20 % of the premium. The result from the Chi-square test shows insignificant, implying that the distribution of farmers’ perception towards full subsidy of agricultural insurance is indifferent across locations. Implication of the study noted that the government and insurer need to socialize the agricultural insurance program more intensively covering premium payment, coverage and claiming.Keywords: production risk, agricultural insurance, farmer’s perception, AUTP, Chi-square